(untitled) (Marketing Jurnali, 2025)
In the context of the green economy, the digitalization of education represents a sustainable alternative to traditional learning systems that often contribute to environmental issue. This article analyzes the role of digital marketing technologies in enhancing the efficiency and ecological sustainability of online education services. Based on qualitative analysis of academic and institutional sources, the study identifies key technologies such as SEO, paid advertising, AI-driven personalization, and social media marketing as major drivers of growth in the online education sector. The results highlight that integrating green marketing principles—such as energy-efficient campaigns, renewable-powered servers, and eco-messaging—can significantly reduce the digital carbon footprint while improving engagement and inclusivity. Recommendations are made to help educational institutions adopt innovative and sustainable marketing strategies that align with global green economy goals.